THE MODERATING EFFECT OF INDUSTRIAL CONTEXT ON THE RELATIONSHIP BETWEEN BRAND EQUITY AND CONSUMER CHOICE IN BRANDED BOTTLED WATER NAIROBI, KENYA - Reuben Kinyuru Njuguna; Muathe Stephen Makau; Francis P. Kerre (European Scientific Journal, ESJ, 2014)
Previous research has shown that brand equity influence consumer choice, however this literature has been limited to broad base view of choice in which specific industry and location characteristic have not been explicitly been examined. This study examines the moderating effect of the Industry context on the relationship between brand equity and consumer choice in the branded bottled water, among supermarkets customers in Nairobi Central Business District, Kenya. The sample size was 400 respondents, comprising of 373 customers and 13 employees of supermarkets. Data was collected using a semi structured questionnaire and an interview guide. Industry context factors influence on the relationship of brand equity influence consumer choice was predicted through the use of a logit model. The research findings indicated that market place efficacy and valence have a moderating role on the influence of brand equity on consumer choice.